PHARMACOLOGICAL POTENTIAL OF POLYHERBAL AYURVEDIC FORMULATIONS – A REVIEW - R NATH, ATHIRA; AWASTHI, VISHESH; K, THAMARA; KUMAR, SOWMYA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Ayurveda is an ancient traditional medical care system. The major aim of Ayurveda is to prevent unnecessary suffering and aiding healthy long life. Ayurveda incorporates natural constituents to make potential medicines that are believed to eliminate the root cause of the diseases. Forty-five thousand plant species are found in the subcontinent of India making it one of the largest biodiversity centers. In India alone, 15,000 medicinal plant species have been reported out of which 7500 species are used by the communities to cure different diseases. Ayurveda uses single or polyherbal for treatment. In these traditional medicine systems, various formulations are prepared one of which is fermented formulations, namely, arishtas and asavas. These formulations are prepared using a decoction of herbal drugs and contain self-generated alcohol. Fermented formulations are known for their stability and efficacy. Indian traditional literature states the usage of these formulations regularly with scientific validation strengthens one immunity and well-being. The current review focuses on Vidangarishta. Punarnavasava, Chandanasava, their preparations, therapeutics uses, and their toxic effects. A thorough understating of these formulations aids in standardizing Ayurveda as a marginalized medicine.